FLAPPERS LIFESTYLE AS REFLECTED IN ‘THE GREAT GATSBY (2013)’ MOVIE - Anindyaputeri, Safira (LANTERN (Journal on English Language, Culture and Literature), 2016)
The era of the 1920s, or often referred to as 'The Roaring Twenties' can be regarded as one of the golden era of the United States after World War I. The result of the golden age was a lifestyle of the women known as 'flapper'. Flapper can be identified by the way they dress and carry themselves, two of which are bob haircut and slim black dresses. Flapper lifestyle is one of the subcultures of the United States is still remembered until today.The writing of the thesis is aimed to identify and analyze flapper’s culture in The Great Gatsby movie produced in 2013. To obtain the desired result, the writer usestextual method with library research as data collecting method. The writer will use definitions and characteristics found in a book titled Flappers: a guide to an American subculture written by Kelly Boyer Sagert. Through analyses in this thesis, the writer concludes that as a long faded American subculture, the culture of flapper still can be seen in The Great Gatsby movie.